2010
DOI: 10.1590/s1678-58782010000500001
|View full text |Cite
|
Sign up to set email alerts
|

An unstructured grid implementation of high-order spectral finite volume schemes

Abstract: The present work implements the spectral finite volume scheme in a cell centered finite volume context for unstructured meshes. The 2-D Euler equations are considered to represent the flows of interest. The spatial discretization scheme is developed to achieve high resolution and computational efficiency for flow problems governed by hyperbolic conservation laws, including flow discontinuities. Such discontinuities are mainly shock waves in the aerodynamic studies of interest in the present paper. The entire r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…27is used to deal with discontinuity in the numerical solution. It is important to note that, when the limiter function is employed to avoid numerical oscillations in non-smooth regions, the piecewise reconstructed high-order polynomial on SVs is noncontinuous, then an approximated Riemann solver must be applied [7,40]. Eq.…”
Section: D Spectral Finite Volume Methodsmentioning
confidence: 99%
“…27is used to deal with discontinuity in the numerical solution. It is important to note that, when the limiter function is employed to avoid numerical oscillations in non-smooth regions, the piecewise reconstructed high-order polynomial on SVs is noncontinuous, then an approximated Riemann solver must be applied [7,40]. Eq.…”
Section: D Spectral Finite Volume Methodsmentioning
confidence: 99%
“…The spectral finite volume (SFV) method of Wang et al 10,11 is used in discretizing the spatial integral terms for higher order spatial accuracy. In the SFV method, the computational domain is divided into finite number (N) of nonoverlapping triangles called spectral volume (SV).…”
Section: Governing Equations and Discretizationmentioning
confidence: 99%
“…Furthermore, in unsteady applications in which such very fine meshes have to be moved in order to accommodate the airfoil motion, previous experience 7 has demonstrated that one ends up with a very stiff aerodynamic solver and, hence, extremely expensive unsteady computations. Therefore, the interest in extending the previously available high-order capability 3,8 in order to treat unsteady flows with moving and/or deforming grids. Although the present work will only consider inviscid flows, the main idea is that the use of high-order methods could lessen the needs for mesh refinement at the solid walls and, hence, reduce computational costs and many of the problems which have been observed in Ref.…”
Section: Introductionmentioning
confidence: 99%